Enhancing Banking Soundness: RGEC Framework Implementation for Risk Management and Corporate Governance in Indonesian Banks – A Comparative Analysis with ASEAN Banking Practices - Asmawardhani, Dewi; Suradana, I Made (Indonesian Journal of Social Research (IJSR), 2026)
Despite Indonesia’s adoption of Basel III standards and high formal compliance with Good Corporate Governance (GCG) (96%), a significant gap remains between regulatory compliance and actual governance effectiveness. This study examines how implementation of the RGEC framework affects banking performance and financial stability in Indonesia compared to ASEAN peers. Using a mixed-methods design, the research combines a systematic literature review and meta-analysis of 68 peer-reviewed studies (2019–2024) with thematic analysis of regulatory documents and banking reports. The results show that integrated risk management has a significant positive effect on banking performance (coefficient: 1.174; p = 0.0003), with credit and operational risks accounting for 67% of performance variance. Three key gaps are identified: (1) a disconnect between GCG compliance and substantive effectiveness, (2) uneven risk governance capacity across bank tiers, and (3) limited integration of emerging risks within RGEC assessments. While Risk Profile, GCG, and Earnings reduce financial distress, Capital shows a paradoxical positive relationship, suggesting that capital adequacy alone is insufficient without strong risk governance. This study introduces a hierarchical risk-impact model tailored to Indonesian banking and proposes an enhanced RGEC+ framework that integrates climate risk, cybersecurity, and fintech disruption. The findings highlight that adopting international standards does not guarantee effective implementation without corresponding organizational capacity and governance quality—an important implication for financial systems in emerging markets.